Far-right extremism online: beyond the fringe - Munk, Tine (Routledge studies in digital extremism, 2024)
"Imparting crucial insights into the digital evolution of far-right extremism and its challenges, this book explores how far-right extremism has transformed, utilizing digital spaces for communication and employing coded language to evade detection. Far-right extremism has spread extensively across online platforms. Flourishing within echo chambers, these groups propagate different types of online and offline actions and advance their hateful ideologies to a wide-ranging audience. Highlighting the intricacies surrounding far-right extremism, distinguishing it from terrorism and examining its contemporary digital manifestations, this study sheds light on how far-right groups utilize online platforms for communication, radicalization, and on-ground actions, relying on alternative truths, misinformation, conspiracy theories, fashion, and memes to connect with like-minded individuals. The book also addresses content moderation challenges and the impact of rising populism in today's political climate, which fuels societal divisions and uncertainty. Far-Right Extremism Online is a valuable resource for academics, students, analysts, and professionals working in counter-extremism, cybersecurity, digital communication, and national security. It is also an indispensable guide for those concerned about far-right extremism in the digital age"--